Digital Readiness Assessment in Islamic Higher Education Institutions with Operationalized BIMAS Framework - Agus Pamuji; Aries Susanty; Budi Warsito; Tonni Agustiono Kurniawan (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2026)
Background: Digital readiness (DR) has become a critical prerequisite for effective digital transformation (DT), particularly as institutions face increasing demands for digital governance, quality assurance, and institutional resilience. These challenges are especially evident in Islamic Higher Education Institutions (IHEIs), where digital transformation must align with regulatory and value-based frameworks. Objective: The purpose of this research is to construct and operationalize the BIMAS framework, comprising Business Model, Infrastructure and Technology, Management and Organization, Audit and Quality Control, and Sustainability and Environment, as an integrated reference for assessing institutional digital readiness. Methods: A Digital Readiness Index (DRI) is developed using a seven-level continuum to classify readiness across BIMAS dimensions and institutional levels. Structural Equation Modeling (SEM) is employed to analyze the causal relationships among the dimensions, complemented by Importance–Performance Map Analysis (IPMA) to identify priority areas for strategic improvement. Results: The findings indicate that Management and Organization (β = 0.378, p < 0.05) and Sustainability and Environment (β = 0,352, p < 0.05) have positive and statistically significant effects on digital readiness, confirming the validity of the BIMAS framework and the proposed DRI. Conclusion: The findings reveal that Management and Organization and Sustainability and Environment exert positive and statistically significant effects on DR; moreover, confirming the validity of the BIMAS framework and the proposed DRI, offering a reliable foundation for guiding DT in IHEIs.